Rehabilitation via HOMe Based gaming exercise for the Upper-limb post Stroke (RHOMBUS): protocol of an intervention feasibility trial. Issue 11 (21st November 2018) - Kilbride, Cherry; Scott, Daniel J M; Butcher, Tom; Norris, Meriel; Ryan, Jennifer M; Anokye, Nana; Warland, Alyson; Baker, Karen; Athanasiou, Dimitrios A; Singla-Buxarrais, Guillem; Nowicky, Alexander
Abstract : Introduction: Effective interventions to promote upper-limb recovery poststroke are characterised by intensive and repetitive movements. However, the repetitive nature of practice may adversely impact on adherence. Therefore, the development of rehabilitation devices that can be used safely and easily at home, and are motivating, enjoyable and affordable is essential to the health and well-being of stroke survivors. The Neurofenix platform is a non-immersive virtual reality device for poststroke upper-limb rehabilitation. The platform uses a hand controller (a NeuroBall) or arm bands (NeuroBands) that facilitate upper-limb exercise via games displayed on a tablet. The Rehabilitation via HOMe Based gaming exercise for the Upper-limb post Stroke trial aims to determine the safety, feasibility and acceptability of the Neurofenix platform for home-based rehabilitation of the upper-limb poststroke. Methods and analysis: Thirty people poststroke will be provided with a Neurofenix platform, consisting of a NeuroBall or NeuroBands (dependent on impairment level), seven specially designed games, a tablet and handbook to independently exercise their upper limb for 7 weeks. Training commences with a home visit from a research therapist to teach the participant how to safely use the device. Outcomes assessed at baseline and 8 weeks and 12 weeks are gross level of disability, pain, objectively measured arm function and impairment, self-reported arm function, passive range of movement, spasticity, fatigue, participation, quality of life (QOL) and health service use. A parallel process evaluation will assess feasibility, acceptability and safety of the intervention through assessment of fidelity to the intervention measured objectively through the Neurofenix platform, a postintervention questionnaire and semistructured interviews exploring participants' experiences of the intervention. The feasibility of conducting an economic evaluation will be determined by collecting data on QOL and resource use. Ethics and dissemination: Ethics approval granted from Brunel University London (10249-MHR-Mar/2018-12322-2). Trial results will be submitted for publication in journals, presented at national and international conferences and distributed to people with stroke. Trial registration number: ISRCTN60291412; Pre-results.